A long-term, open-label study of valbenazine for tardive dyskinesia. (18th August 2021) - Lindenmayer, Jean-Pierre; Verghese, Cherian; Marder, Stephen R.; Burke, Joshua; Jimenez, Roland; Siegert, Scott; Liang, Grace S.; O'Brien, Christopher F.
Abstract: Background: Individuals with tardive dyskinesia (TD) who completed a long-term study (KINECT 3 or KINECT 4) of valbenazine (40 or 80 mg/day, once-daily for up to 48 weeks followed by 4-week washout) were enrolled in a subsequent study (NCT02736955) that was primarily designed to further evaluate the long-term safety of valbenazine. Methods: Participants were initiated at 40 mg/day (following prior valbenazine washout). At week 4, dosing was escalated to 80 mg/day based on tolerability and clinical assessment of TD; reduction to 40 mg/day was allowed for tolerability. The study was planned for 72 weeks or until termination due to commercial availability of valbenazine. Assessments included the Clinical Global Impression of Severity-TD (CGIS-TD), Patient Satisfaction Questionnaire (PSQ), and treatment-emergent adverse events (TEAEs). Results: At study termination, 85.7% (138/161) of participants were still active. Four participants had reached week 60, and none reached week 72. The percentage of participants with a CGIS-TD score ≤2 (normal/not ill or borderline ill) increased from study baseline (14.5% [23/159]) to week 48 (64.3% [36/56]). At baseline, 98.8% (158/160) of participants rated their prior valbenazine experience with a PSQ score ≤2 (very satisfied or somewhat satisfied). At week 48, 98.2% (55/56) remained satisfied. Before week 4 (dose escalation), 9.4% of participants had ≥1 TEAE. After week 4, the TEAE incidence was 49.0%. No TEAE occurred in ≥5% of participants during treatment (before or after week 4). Conclusions: Valbenazine was well-tolerated and persistent improvements in TD were found in adults who received once-daily treatment for >1 year.